Role of physiological evacuation in health preservation: a narrative review - M. Misbahuddin; M. Tanwir Alam; Jamal Akhtar (International Journal of Research in Medical Sciences, 2026)
Physiological evacuation (Istifrāgh-e-tabī) is an essential physiological process described in Unani medicine through which the body naturally eliminates Fuḍlāt (metabolic waste products) generated during digestion and metabolism. Proper physiological evacuation is considered crucial for maintaining humoral equilibrium, preserving Ḥarārat Gharīzī (innate heat), and preventing disease. This narrative review examined Unani literature alongside contemporary biomedical evidence retrieved from PubMed, Scopus, ScienceDirect, Web of Science, Google Scholar, and the AYUSH Research Portal. The literature was critically analyzed to explore the formation of Fuḍlāt, the concept of Huḍūm Arba‘a, and the physiological pathways of waste elimination, including gastrointestinal, renal, respiratory, cutaneous, and secretory routes. Classical Unani descriptions of Barāz (feces), Bawl (urine), Ḥayḍ (menstruation), ‘Araq (sweat), Laban (breast milk), Tanaffus (respiration), Lu‘āb (saliva), and Ānsū (tears) were found to correspond conceptually with modern physiological mechanisms responsible for removing carbon dioxide, urea, uric acid, creatinine, bile pigments, excess electrolytes, and inflammatory metabolites. Effective physiological evacuation supports metabolic homeostasis, immune regulation, acid–base balance, thermoregulation, and tissue health, whereas impaired clearance contributes to oxidative stress, inflammation, and metabolic dysfunction. The review demonstrates a strong conceptual similarity between Unani principles and modern biomedical understanding of physiological waste elimination, highlighting the potential relevance of Istifrāgh-e-Ṭabī in preventive and integrative healthcare.